2014
DOI: 10.1074/jbc.m114.585869
|View full text |Cite
|
Sign up to set email alerts
|

High Salt Concentrations Increase Permeability through OmpC Channels of Escherichia coli

Abstract: Background: OmpC porin is less permeable than OmpF, but there is little difference in channel size. Results: There are more charged residues in the OmpC channel, and mutating them or increasing ionic strength made it more permeable and OmpF-like. Conclusion: Charged residues produce the low permeability of OmpC. Significance: OmpC, produced in a high ionic strength environment, has properties optimized for this environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
79
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(85 citation statements)
references
References 38 publications
6
79
0
Order By: Relevance
“…The authors suggested that, in contrast to the obvious exclusion due to reduced channel size, effects such as changes in the electric field at the constriction zone might have an impact on the channel permeability (17). Recent computational and experimental studies also suggested that the electrostatic profile inside the channel might play a major role in transit of polar molecules (18,19). Subsequently, the internal electrostatics of the mutant porins (OmpC20 and OmpC33) were analyzed in the absence of any antibiotic or metabolite, using water as a probe to sense the internal electric field (20).…”
mentioning
confidence: 99%
“…The authors suggested that, in contrast to the obvious exclusion due to reduced channel size, effects such as changes in the electric field at the constriction zone might have an impact on the channel permeability (17). Recent computational and experimental studies also suggested that the electrostatic profile inside the channel might play a major role in transit of polar molecules (18,19). Subsequently, the internal electrostatics of the mutant porins (OmpC20 and OmpC33) were analyzed in the absence of any antibiotic or metabolite, using water as a probe to sense the internal electric field (20).…”
mentioning
confidence: 99%
“…This construct was then inserted into pHSG575. The construction of pHSG575-based expression plasmids for E. coli ompF and ompC genes has been described earlier (13).…”
mentioning
confidence: 99%
“…This can also account for the low permeability of OmpC for anionic b-lactams [102,103]. Moreover, the replacement of all ten titratable residues that differ between OmpC and OmpF in the pore-lining region leads to the exchange of antibiotic permeation properties [104]. Together, these structural and functional data clearly demonstrate that the charge distribution at pore linings, but not pore size, is a critical parameter that physiologically distinguishes OmpC from OmpF.…”
Section: Porin Alterations In Clinical Isolatesmentioning
confidence: 98%